A STUDY OF HEMATOLOGICAL PROFILES IN CHRONIC LIVER DISEASE WITH SPECIAL REFERENCE TO ANEMIA, THROMBOCYTOPENIA, AND LEUKOPENIA - Dr.Manjeet Singh; Dr.Ajay Pal Singh; Dr.Vedant Sharma (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: Chronic liver disease (CLD) is a progressive disorder associated with significant morbidity and mortality due to hepatic and extrahepatic complications. Hematological abnormalities such as anemia, thrombocytopenia, and leukopenia are frequent in CLD and often correlate with disease severity. These simple, cost-effective parameters may provide valuable insight into prognosis and clinical outcomes, especially in resource-limited settings. Aim and Objective: This study aimed to evaluate the hematological profile of CLD patients, with special reference to the prevalence and patterns of anemia, thrombocytopenia, and leukopenia, and to assess their correlation with clinical features and disease severity. Materials and Methods: A prospective cohort study was conducted in the Department of General Medicine, G.R. Medical College, Gwalior, from April 2023 to September 2024. One hundred patients aged 18–60 years with CLD confirmed by ultrasonography were enrolled using purposive sampling. Patients with comorbidities, pregnancy, or prior anemia treatment were excluded. Hematological indices, peripheral smear findings, and biochemical parameters were recorded and statistically analyzed. Results: Moderate anemia was most common (37%), followed by severe (20%) and mild (16%). Normocytic normochromic morphology predominated (45%), with macrocytic and microcytic variants also present. Thrombocytopenia occurred in 52%, significantly associated with severe anemia (p < 0.001) and complications like hematemesis and ascites. Leukopenia was infrequent, while mortality reached 12%. Hypoalbuminemia showed strong correlation with advanced disease severity, underscoring its prognostic value. Conclusion: Anemia and thrombocytopenia are highly prevalent in CLD and correlate with clinical severity. Peripheral smear analysis remains a valuable, low-cost diagnostic adjunct. Hematological profiling should be integrated into routine CLD management for early risk stratification and prognostic evaluation.